Development of a questionnaire measuring treatment concerns in regular dental patients - Klages U, Sadjadi Z, Lojek LD, Rust G, Wehrbein H. (Journal compilation, 2008)
The aim of this study was to develop an instrument measuring core concerns about dental treatment guided by Reiss’ expectancy theory of fear.